Effect of Natural Hazards on Types of Landslide - Namdar, Abdoullah; Fadzil, Mat Yahaya (Electronic Journal of Geotechnical Engineering, 2014)

(untitled)
To improve human settlement, the behavior of geo-hazard requires to be investigated. The geological, geotechnical and geomorphological of site, plays important role in occurrence of landslide. The rainfall, earthquake, erosion, tectonic features, major uplift, hurricanes, construction activities, sand/silt boiling air, volcanic gases, impulsive waves, and snowmelt are among the important factor in trigger of landslide. Authors made an attempt to review landslide phenomenon with consideration some important factors in trigger types of landslide.